Hubungan Antara Religiusitas Dengan Perilaku Seks Bebas Pada Remaja - Sumarni Sumarni; Surmiasih Surmiasih; Anggi Kusuma; Rizki Yeni Wulandari (Universitas Muhammadiyah Pekajangan Pekalongan, 2025)
Free sexual behavior among adolescents is influenced by the level of religiosity, as religious values and beliefs serve as a foundation for behavior formation. The high prevalence of free sexual behavior among Indonesian adolescents 59% among females and 74% among males aged 15–19 yearshighlights the importance of religiosity as a contributing factor. This study aimed to examine the relationship between religiosity and free sexual behavior among adolescents at State Junior High School 1 Ambarawa, Pringsewu Regency.This study employed a quantitative research method with a correlational design using a cross-sectional approach. The population consisted of 232 students at State Junior High School 1 Ambarawa, with a sample of 147 respondents. The study was conducted on September 9, 2025. Probability sampling was applied using the Proportional Stratified Random Sampling technique. Data were analyzed using the gamma statistical test.The results showed a significant relationship between religiosity and free sexual behavior, with a p-value of < 0.001 and a correlation coefficient (r) of 0.390. These findings indicate that the research hypothesis was accepted, demonstrating a negative relationship between religiosity and free sexual behavior among adolescents at State Junior High School 1 Ambarawa. This suggests that higher levels of religiosity are associated with lower levels of free sexual behavior, and vice versa.It is expected that schools collaborate with community health centers to provide reproductive health education for adolescents in order to enhance their knowledge and to reactivate religious extracurricular activities.